Implementation of Standard Physiotherapy Service Policies In Puskesmas: Literature Review - Intana Fernando, Shava; Jeanette Jacqueline, Regina; Fatimatuzahroh, Fatimatuzahroh; Nur Alpiah, Dini (International Journal of Social Research, 2024)
The increase in non-communicable diseases such as hypertension, stroke, diabetes, joint disease, lack of physical activity, injury and disability responds to the increasing public need for physiotherapy services in health facilities, including community health centers. Many public health problems have not been resolved and non-communicable diseases continue to increase. Prevention of this disease starts with primary health care. In accordance with Minister of Health Regulation Number 65 of 2015, physical therapy is included in the first level of service. The role and duties of physiotherapists at community health centers according to Minister of Health regulation no. 65 of 2015, namely the implementation of promotive and preventive activities, without neglecting treatment and rehabilitation. The availability of physiotherapy services at city health centers encourages the availability of physiotherapy services for people who need general physiotherapy services by prioritizing, supportive and preventive services.